ANALISIS EFISIENSI PERBANKAN SYARIAH DUNIA - Khalidah, Nur Diana; Zuhroh, Idah (Program Studi Ekonomi Pembangunan, 2023)
In the last decade the development of sharia banking in the world has increased. One of the important things to measure banking performance is to look at the level of efficiency. This research aims to estimate the efficiency of Islamic banking in the world and analyze the factors that influence it. The research object consists of ten Islamic banks in the world with the period first quarter 2014 - fourth quarter 2021. The analysis technique in this research uses panel data regression analysis to analyze the factors that influence banking efficiency. The research results show that in general sharia banking in the world is not operating efficiently. The regression estimation results show that CAR and ROA have a significant effect on the efficiency of Islamic banking in the world. Meanwhile, NPF does not have a significant effect on the efficiency of sharia banking in the world.